PENGEMBANGAN MEDIA PANLINTARMATIKA (PAPAN PERKALIAN PINTAR MATEMATIKA) MATERI PERKALIAN UNTUK SISWA SEKOLAH DASAR - Hasna Nur Afifah; Meita Fitrianawati (PGSD Universitas Muria Kudus, 2021)
This study aims to 1) find out the steps in developing Panlintarmatika learning media, 2) know the feasibility of developing Panlintarmatika learning media based on experts. This study is a type of Research and Development (R and D) research using the Borg and Gal model which consists of: (1) research and information collecting, (2) planning, (3) developing preliminary from a product, (4) prelimunary field testing, (5) main product revision, (6) main field testing, (7) operational product revision (8) operational field testing. The trial subjects used were 18 grade 2 students and teachers at SD N Kalangan. Data collection techniques in the form of observation, interviews and questionnaires. Data analysis includes quantitative data analysis and qualitative data analysis. The results showed that the validation of the media experts received a score of 60 in the